Physico-chemical features of water in Betana wetland, Belbari, Morang, Nepal - Thapa, Ganesh Bahadur; Pal, Joydeb (Himalayan Journal of Science and Technology, 2018)
Different physico-chemical parameters in Betana wetland pond water was studied for two years. Air temperature showed positive and significant correlation with water temperature (r =0.947, P<0.01) but it had inverse and significant correlation with free CO2 (r = -0.685, P<0.05), pH (r = -0 .653, P<0.05) and DO (r = -0.582, P<0.05). The water temperature showed positive and significant correlation with phosphate (r =0.635, P<0.05) but it showed inverse and significant correlation with pH (r = -0.692, P<0.05), DO (r = -0.576, P<0.05) and free CO2 (r = -0.798, 2 P<0.01). Free CO2 showed inverse and significant correlation with chloride (r = -0.596, P<0.05). BOD showed no significant positive correlation but it had inverse and significant correlation with pH (r = -0.613, P< 0.05). Total acidity (TA) showed positive and significant correlation with total hardness (TH) (r = 0.580, P<0.05) but inverse and significant correlation with water temperature (r = -0.623, P<0.05) and phosphate (r = -0.608, P<0.05). All physico-chemical parameters of Betana pond water were within permissible range for wild fish and fish culture. Outbreak of any fish diseases did not occur during Nov. 2008-Oct. 2010. Being ecotourism area, maintenance of water quality should be done by periodic evaluation of physico-chemical parameters of the pond water.